Disfruto de lo que me gusta - Aguirre Campos, Elida Elsa (2018)
Through the development of this Learning Activity it is intended that 3-year-old students of the Initial level, recognize their feelings, needs, interests and limitations and express through words, actions, gestures and movements. The active participation of the students will be taken into account when carrying out the actions proposed by the Teacher and by themselves, the diverse way of expressing their feelings, and the way in which the students act when working in a group. They will be encouraged to participate in games, expression orally and in their mother tongue, discover sensations through their senses and achieve their autonomy. The motivating game is "The Magic Roads" with it I hope that the expected purposes are achieved.